Tunable photoluminescence and energy transfer in Dy3+ and Eu3+ co-doped NaCaGd(WO4)3 phosphors for pc-WLED applications - Ekim, Utku; Kachou, Ikhlas; Kallel, Tarak; Dammak, Mohamed; Ersundu, Miray Celikbilek; Ersundu, Ali Ercin (ROYAL SOC CHEMISTRY, 2025)
Elevated temperatures can lead to reabsorption and color drift, compromising the quality of phosphor-converted white light-emitting diode (pc-WLED) devices. To ensure the performance of WLEDs under these conditions, it is essential to develop luminescent materials that maintain stable color. Consequently, there is a pressing need for single-phase white-emitting phosphors with robust chromatic stability. In this work, we synthesize a series of color-tunable NaCaGd(WO4)3 (NCGW) phosphors using conventional solid-state reaction method, co-doping with Dy3+ and Eu3+ in varying ratios. X-ray diffraction, Rietveld refinement and scanning electron microscopy analyses are carried out to identify the phase purity and morphology. The photoluminescence (PL) properties are investigated under excitations of 352 nm and 393 nm. The PL emission spectra and fluorescence decay curves reveal efficient energy transfer between the Dy3+ and Eu3+ ions within the NCGW host, demonstrating tunable PL emission properties through manipulation of this energy transfer. At elevated temperatures of up to 200 degrees C, the positions of the characteristic emission peaks of Dy3+ and Eu3+ in NCGW phosphors remain essentially unchanged. Although the emission band intensities decrease due to thermal quenching, they retain a significant portion of their initial intensity compared to room temperature levels. For proof-of-concept studies, a single-phase NCGW:0.05%Dy3+-0.05%Eu3+ phosphor is combined with a commercial 365 nm UV chip to create a WLED device prototype. This prototype achieves a color rendering index of 81.7, a correlated color temperature of 4862 K and Commission International de I'Eclairage chromaticity coordinates of (0.35, 0.37), exhibiting comparable or superior colorimetric values to those reported in previous research. The results indicate that Dy3+ and Eu3+ co-doped NCGW phosphors, with their high chromaticity stability, have significant potential for full-spectrum WLED applications.
Keywords: RED; LUMINESCENCE; EFFICIENT; Chemistry